The Relationship Between Political Efficacy and Online Political Participation Among Women: A Systematic Literature Review - Yu Liu; Ku Hasnita Ku Samsu; Yok Fee Lee; Mohd Mahadee Ismail (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (223-235)